Novel insights into electrical double layers in carbonate reservoirs under low-salinity water injection using molecular dynamics simulation - Saifali Al-Musawi; Fariborz Rashidi; Sepideh Amjad-Iranagh (Scientific Reports)
Abstract Understanding how mineral heterogeneity and brine salinity influence the electrical double layer (EDL) structure is crucial for optimizing low-salinity water injection strategies in carbonate reservoirs. In this study, molecular dynamics (MD) simulations were conducted to elucidate the mechanisms governing EDL behavior at the interface of a novel composite carbonate surface (87% calcite, 13% quartz) in contact with diluted water (DW), seawater (SW), and high-salinity formation water (FW) in presence of complex model oil including wide variety of nonpolar oil hydrocarbon. Results indicated that increasing brine salinity compressed the Stern layer significantly, strengthening electrostatic interactions at the mineral surface and promoting oil adhesion due to enhanced ion bridging by divalent cations (Ca²⁺, Mg²⁺). This process resulted in a pronounced shift toward hydrophobic (oil-wet) surface characteristics under FW conditions, compared to SW and DW. Additionally, the observed differences in water–surface interactions between calcite and quartz were explained mechanistically: the highly charged calcite surface enabled strong inner-sphere coordination of water molecules at 2.37 Å, whereas the neutral quartz surface supported only weaker outer-sphere hydration at 3.1 Å. Ion mobility analysis further revealed enhanced dynamics of Na⁺ ions in SW system, facilitating disruption of oil–surface ionic bridges, while FW promoted ion clustering and reduced ionic mobility, stabilizing oil attachment. These insights emphasize the critical role of mineral surface chemistry and salinity-dependent electrostatic interactions in governing wettability and oil recovery efficiency during low-salinity waterflooding.